Culture and social: herbal medicine as health communication to build urban community empowerment - Suharti, Bangun; Kartika, Tina; Sugiyanta (Jurnal Studi Komunikasi, 2021)
This article discusses culture and social issues in the community related to herbal medicine used for health communication and community empowerment in Bandar Lampung. Additionally, herbal medicine plays a significant role in empowering families from the dependence of conventional medicine and developing traditional medicine. A good health level of community is an asset of Indonesia's human development that is independent, healthy, and strong. Using the qualitative research approach, the data source consisted of interviews, deep observations, and documentation. The results are herbal medicine 1) empowers the community for better family finance, 2) empowers people to get a job, 3) creates a new paradigm, making herbal medicine the first treatment choice when one is sick, instead of conventional medicine (medics). This study's findings describe the culture of the Indonesian people who are accustomed to drinking herbal medicine. Therefore, traditional herbal medicine needs to be empowered as a unique Indonesian culture, as it is possible to combine herbal and conventional medicines. This research contributes to policymakers to make herbal treatment models holistically, to support Program Indonesia Sehat (Indonesian General Health Program).